Another place in time eaudiobook - Nubie, Steve (Twilight Zone Radio Dramas., 2013)
A physicist on a remote island in the Irish Sea finds a link to multiple dimensions. Contemporary science refers to them as parallel universes. Two people find out the hard way that the grass isn't always greener on the other side.